Students’ Perceptions on Zoom Digital Media in Learning Speaking at SMP IT Fathona Palembang - Rinda Ismadella (Ta'dib: Jurnal Pendidikan Islam, 2022)
The aim of this study was to find out how students perceived the use of Zoom application in learning speaking. This study used qualitative study as its method. Five eighth-grade students from SMP IT Fathona Palembang took part in this study. They were chosen purposively. The data from the interview was evaluated using thematic analysis. There were 4 categories of students’ perception on Zoom digital media in learning speaking: 1) helpful in learning speaking; 2) costly application; 3) difficulty in internet connection; and 4) aspects of learning speaking. Finally, the findings revealed that the majority of students enjoy and are more engaged in learning speaking taught by using Zoom application.